Tourists’ attitude matters for the international travelling intention to Malaysia: a study on tourism quality experience and travel frequency as determinant factors - Saad, Mazni; Omar, Azizah; Azman Ong, Mohd Hanafi; Tiwari, Veenus (Universal Publishers - Boca Raton, Florida, USA, 2022)
Purpose: This study explores the mediating role of attitude on tourism quality experience and travel frequency as the determinants of international tourists' intention to visit Malaysia. Design/methodology/approach: This study used the quantitative survey analysis methodology to develop and test a structural model with partial least squares (PLS-SEM). Findings: This study investigates the concepts of creating a positive tourist attitude to build a destinations' image, using Travel frequency that relies on traditional forms of travelling. The study highlights the importance of examining the influence of a credible and valuable source that can help build tourist quality experience towards a destination and its impact on the audience's intention to revisit the destination in Malaysia. Research limitations/implications: The population of this study was limited to international tourists who visited tourism destinations in Malaysia. Therefore, the results from this study may not be generalised beyond this population. Practical implications: The findings will help highlight the methods to develop destinations' revisit intention of travellers with their perceptions towards destination attributes and quality of experience. Originality/value: This research reveals the underlying procedure of forming tourists' intention for taking their perception of experience quality, tourist attitude, and visit intention with a latent construct of travel frequency.